Exploring the Relationship between Teacher Professional Development and Student Learning Outcomes - Dewi, A. Erni Ratna; Kalil, Nur Cahyani; Hidayat, Hidayat; Juniati, Sri Rahayu (Journal of Pedagogi, 2024)
Teacher professional development is a key factor in improving education quality and student learning outcomes. This study aims to explore the relationship between teacher professional development and student learning outcomes and identify factors that influence the effectiveness of professional development programs. The method used in this research is a literature review that includes analyzing various studies related to teacher professional development and its impact on student learning outcomes. This study collected data from relevant articles, journals and research reports. The results of the review show that teacher professional development contributes significantly to improving student learning outcomes through improving pedagogical competence, technology utilization and classroom management. However, there are obstacles such as a lack of teacher motivation that affects the effectiveness of the program. This study provides important implications for stakeholders, showing the need for collaboration between the government, educational institutions and teachers in creating a sustainable professional development system. With adequate support, it is expected that professional development can effectively improve the quality of education and student learning outcomes, as well as create a learning environment that is more inclusive and responsive to students' needs.